Muscle-sparing aortic coarctation repairCentral MessagePerspective - Stephanie G. Berset, MD; Hitendu Dave, MD; Christian Balmer, MD; Anna Nowacka; Raymond Pfister, MD; Patrick O. Myers, MD; René Prêtre, MD (JTCVS Techniques)
Objective: Surgery for aortic coarctation repair provides excellent hemodynamic results but may be complicated by musculoskeletal issues. The purpose of the study was to determine the midterm results of a muscle-sparing surgical approach to aortic coarctation repair, with special emphasis on the repair and on the musculoskeletal changes associated with a posterior thoracotomy. Methods: We included all children with aortic coarctation operated on with our minimally invasive approach between June 2002 and October 2004, with a follow-up of ≥4.5 years. Patients were assessed clinically and echocardiographically. The spine, left chest, and shoulder were assessed clinically and radiographically. Results: Thirty-one children were included. The age at operation ranged from 1 day to 15 months and weight ranged from 980 g to 10 kg. All patients underwent an extended end-to-end anastomosis coarctation repair through a minimal (n = 19) or total-muscle sparing (n = 12) or extrapleural (n = 18) approach. Five patients had an additional enlargement procedure on the aortic arch. 27 patients had no residual or recurrent gradient. Four patients exhibited restenosis, for which 1 underwent a percutaneous angioplasty and 2 underwent surgical reintervention. All patients were free of hypertension. One patient had borderline values. The musculoskeletal assessment was normal in all but 3 patients. Two patients who underwent other subsequent thoracic surgeries developed thoracogenic scoliosis of moderate severity. A third patient had a left winged scapula. No rib fusion or intercostal space enlargement was found. Conclusions: Compared with a conventional approach, our minimally invasive surgical approach led to excellent musculoskeletal outcomes without compromising the hemodynamic results.